2014
DOI: 10.1007/s00464-014-3815-0
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal transsphenoidal surgery of 1,166 pituitary adenomas

Abstract: AimTo report the results of a series of patients undergoing pure endoscopic endonasal pituitary surgery and to evaluate the efficacy and safety of this procedure.Materials and methodsThe data of 1,166 patients that underwent endoscopic endonasal transsphenoidal adenoma removal between December 2006 and June 2013 were retrospectively reviewed. Pre- and postoperative hormonal status (3 months after surgery) were analyzed and compared with the clinical parameters originally presented by the patients. The incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
89
3
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 28 publications
9
89
3
2
Order By: Relevance
“…4,[13][14][15][16][17][18][19][20][21][22][23] Previously reported rates of readmission range from 0.7% to 1.8% for epistaxis, 2.9% to 6.4% for hyponatremia, and 0.6% to 4% for CSF leak. [13][14][15][16][17][18][19]23 As clinical management of each complication varies among health care systems, it is difficult to extrapolate our 30-day readmission rate to estimate the associated costs at other institutions. Similarly, as surgical technique also varies among surgeons, it is difficult to estimate the overall average 30-day readmission rate among all hospitals based on this study alone.…”
Section: Discussionmentioning
confidence: 99%
“…4,[13][14][15][16][17][18][19][20][21][22][23] Previously reported rates of readmission range from 0.7% to 1.8% for epistaxis, 2.9% to 6.4% for hyponatremia, and 0.6% to 4% for CSF leak. [13][14][15][16][17][18][19]23 As clinical management of each complication varies among health care systems, it is difficult to extrapolate our 30-day readmission rate to estimate the associated costs at other institutions. Similarly, as surgical technique also varies among surgeons, it is difficult to estimate the overall average 30-day readmission rate among all hospitals based on this study alone.…”
Section: Discussionmentioning
confidence: 99%
“…Overall postoperative CSF leak and bacterial meningitis rates in 9 recent large endoscopic pituitary adenoma series (all with over 200 patients) have ranged from 0.6% to 5%, and 0% to 3.4%, respectively. NSF usage in these series ranges from 1% to 43% and planned lumbar CSF drainage from 0.6% to 21.7% …”
Section: Intradural Tumorsmentioning
confidence: 97%
“…Although a majority of the cases reported non‐endoscopic approaches, multiple studies have shown a trend toward the endoscopic approach in order to maximize exposure. This is especially true in academic centers . Additional studies have shown the safety and efficacy of endoscopic approaches for the removal of sinonasal tumors .…”
Section: Discussionmentioning
confidence: 99%